Astrocyte Hypertrophy and Microglia Activation in the Rat Auditory Midbrain Is Induced by Electrical Intracochlear Stimulation - Rosskothen-Kuhl, Nicole; Hildebrandt, Heika; Birkenhäger, Ralf; Illing, Robert-Benjamin (Frontiers in Cellular Neuroscience, 2018)
Neuron-glia interactions contribute to tissue homoeostasis and functional plasticity in the mammalian brain, but it remains unclear how this is achieved. The potential of central auditory brain tissue for stimulation-dependent cellular remodeling was studied in hearing-experienced and neonatally deafened rats. At adulthood, both groups received an intracochlear electrode into the left cochlea and were continuously stimulated for 1 or 7 days after waking up from anesthesia. Normal hearing and deafness were assessed by auditory brainstem responses. The effectiveness of stimulation was verified by electrically evoked auditory brainstem responses as well as immunocytochemistry and in situ hybridization for the immediate early gene product Fos on sections through the auditory midbrain containing the inferior colliculus (IC). Whereas hearing-experienced animals showed a tonotopically restricted Fos response in the IC contralateral to electrical intracochlear stimulation, Fos positive neurons were found almost throughout the contralateral IC in deaf animals. In deaf rats, the Fos response was accompanied by a massive increase of GFAP indicating astrocytic hypertrophy, and a local activation of microglial cells identified by IBA1. These glia responses led to a noticeable increase of neuron-glia approximations. Moreover, staining for the GABA synthetizing enzymes GAD65 and GAD67 rose significantly in neuronal cell bodies and presynaptic boutons in the contralateral IC of deaf rats. Activation of neurons and glial cells and tissue re-composition were in no case accompanied by cell death as would have been apparent by a Tunel reaction. These findings suggest that growth and activity of glial cells is crucial for the local adjustment of neuronal inhibition to neuronal excitation.